The concept of shrewdness: its function in the philosophical method - Caimi, Mario (Estudios de Filosofía, 2013)
In Anthropology, in the section that refers to higher cognitive faculties, shrewdness is presented as the gift of inquiry. This indicates that it has a place in scientific research. In our work we examine the role that can be attributed to shrewdness in the research method. The presence of shrewdness in a researcher is contingent, but it can be considered as a condition that determines the scope of the method and its limits. It also determines some features of the results of an investigation. Therefore, we suggest that shrewdness is an accessory condition of the method. The scientist’s personal intelligence is thus a critical element in the research, both in the posing of its purposes, and in the progress of work, and especially in the design stages of invention and discovery.